Automatic subtitle generation for Bengali multimedia using deep learning - Rhythm, Ehsanur Rahman; Arnob, Shafakat Sowroar; Shuvo, Rajvir Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.